El problema de Integración simbólica. - Ulate Ramírez., Carlos Ml. (2012)
Through this research the heuristic or analytical rules that engineers, mathematicians and students of mathematics use when they must find a primitive (or antiderivative3). Therefore, an explanation of the type of procedure that the professional or future professional, in case of students, gives to certain integral is provided. This information was obtained by classifying the information of a survey done to a population of twenty persons: five students of second year of mathematics, five students of fourth year of mathematics, five mathematicians and five engineers, all members of the university community of the University of Costa Rica.